ESRA19-0213 The analgesic efficacy of PECS2 block following radical mastectomy: a randomised, controlled, triple-blinded trial. (30th August 2019) - Aljabari, A; Baeriswyl, M; El-Boghdadly, K; Albrecht, E
Abstract : Background and aims: The pectoral nerves 2 (PECS2 ) block is a regional anaesthetic technique developed to relieve pain after breast surgery, but efficacy data following radical mastectomy are scarce. This randomised controlled triple-blinded trial tested the hypothesis that PECS2 block would provide effective analgesia after radical mastectomy. Methods: 50 patients scheduled for radical mastectomy under general anaesthesia were randomly allocated either to receive a PECS2 block or receive no block, after induction of general anaesthesia. Perioperative multimodal analgesia consisted of dexamethasone, magnesium, paracetamol, ibuprofen and intravenous morphine patient-controlled analgesia, following a pre-defined protocol. the primary outcome was intravenous morphine consumption at 24 h postoperatively. Secondary outcomes were cumulative intravenous morphine consumption at 2 and 48 postoperative hours, visual analogue pain scores at rest at 2, 24 and 48 postoperative hours, presence of postoperative nausea and vomiting and pruritus at 24 and 48 postoperative hours, and presence of chronic pain at 6 postoperative months. Results: Demographic data were equivalent in both groups (table 1 ). Mean intravenous morphine consumption at 24 postoperative hours was significantly reduced in the PECS2 (5.0 mg, 95%CI:2.5–7.5) compared to the control group (9.7 mg, 95%CI:5.8–13.7, p=0.04). the secondary pain outcomes were also similar between groups (table 2 ), with the exception for intravenous morphine consumption at 48 postoperative hours in favour of the PECS2 group (6.0 mg, 95% CI:2.7–9.2) compared to the control group (12.5 mg, 95% CI:6.7–18.8, p=0.04). Conclusions: The PECS2 block provides modest postoperative analgesia in the setting of perioperative multimodal analgesic treatment after radical mastectomy, without impact on chronic postoperative pain.